Legal Review of Legalization and Waarmerking by Indonesian Notary - Wahid Mahbub; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Notary is a Public Official who is authorized to make authentic deeds and has other powers as referred to in this law or based on other laws according to the Law on Notary Position Number 30 of 2004 jo. Act No. 2 of 2014 in particular Article 15 paragraph 2 letters a and b, namely: Notaries have the authority to ratify signatures and determine the certainty of the date of the letter under hand by registering in a Special book and affixing the letter under hand by registering in a special book. One example is the case Number: 174 / Pdt.G / 2009 / PN.SMG. Jo. Number: 356 / Pdt / 2010 / PT.SMG. Jo. Number: 1245 K / Pdt / 2011 / MA. Notary was made a co-defendant in issuing Deed Number: 3 dated June 22, 2004 concerning the Minutes of the GMS with the agenda of meeting amendments to the company's articles of association and Deed Number: 7 dated 21 July 2005 regarding the Minutes of the GMS with the agenda of the approval meeting for the transfer of shares as well as the Deed Number: 8 dated 21 July 2005 and the Deed Number: 9 dated 21 July 2005 regarding the sale and purchase of shares. The aforementioned Deed is drawn up based on a power of attorney legalized by a Notary Number: 434 / L / 2005. The problems can be formulated how the implementation of legalization and Waarmerking is carried out by a Notary in Indonesia and what is the responsibility of the Notary in carrying out legalization and Waarmerking of deeds under hand in Indonesia and also what are the consequences of legalization and Waarmerking of the deed in under the hands of a Notary in Indonesia. The research used is a normative legal approach (normative legal research). And the results is that the implementation of legalization and Waarmerking carried out by a Notary in Indonesia in case Number: 174 / Pdt.G / 2009 / PN.SMG. Jo. Number: 356 / Pdt / 2010 / PT.SMG. Jo. Number: 1245 K / Pdt / 2011 / MA. Formally, it has fulfilled the requirements for the form and type of deed as stipulated in the Law on Notary Position Number 30 of 2004 Jo. Law on Notary Position Number: 2 of 2014.